Research and policy in ethnic relations compromised dynamics in a neoliberal era - Husband, Charles 1944- (The Policy Press, 2015)
This unique book explores the interaction between the academic research community and those who use its research to inform their social policy interventions, thus raising awareness of the linkages between research and social policy, particularly in the area of ethnic relations
Title from publisher's bibliographic system (viewed on 10 Mar 2022)
Keywords: Ethnic relations / Research / Great Britain; Race relations / Research / Great Britain; Great Britain / Race relations / Government policy